Rekonseptualisasi Kesejahteraan Anak dalam Konteks Kebijakan Sosial: Antara Pendekatan Kesejahteraan, Hak Anak, dan Partisipasi: Reconceptualizing Child Welfare in the Context of Social Policy: Between Welfare, Children's Rights, and Participation Approaches - Herbowo, Heru Dwi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The approach to child welfare has shifted from an assistance-based model to a rights-based approach and active participation in social policy. This study aims to analyze the ideal child welfare model that integrates the fulfillment of basic rights, legal and social protection, and children's participation in public policy. The research method used is a literature study that analyzes various academic literature, national and international policies, and reports of global organizations such as UNICEF and WHO in the period 2020-2024. The results showed that countries that implemented a child rights-based welfare model experienced significant improvements in access to education, health, and children's participation in policies. However, in Indonesia, challenges remain, such as the stunting rate, which still reached 21.6% in 2022, and the low participation rate of children in social policies, which was only 30% in 2023. The conclusion of this study confirms that the implementation of a more inclusive and sustainable child welfare model requires strengthening rights-based policies, increasing the role of society in child protection, and utilizing technology to increase children's participation in social policies.